2022
DOI: 10.3389/fphar.2022.841818
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-inflammatory Properties of Resveratrol in Diabetic Nephropathy: A Systematic Review and Meta-analysis of Animal Studies

Abstract: Background: Accumulated experimental evidence suggests that resveratrol may have an effect on diabetic nephropathy by inhibiting inflammation and decreasing oxidative stress. However, the credibility of the evidence for this practice is unclear. Thus, we aimed to perform a systematic review and meta-analysis of animal studies to evaluate the antioxidant and anti-inflammatory properties of resveratrol when used in the treatment of diabetic nephropathy.Methods: Electronic bibliographic databases including PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…Clinical trial revealed that the combination of resveratrol (500 mg/d) with Losartan (12.5 mg/d) reduced the urinary albumin-creatinine ratio (UACR) (–46.4 mg/g, 95% CI: −64.5 to −28.3 vs 29.9 mg/g, 95% CI: 4.9 to 54.9; p < 0.001) and increased the activity of antioxidant enzymes [ 72 ]. A meta-analysis involving 36 animal studies demon strated that resveratrol exerted its antioxidant effects by means of reducing malondialdehyde (MDA) level and restoring activities of SOD, CAT, GSH and GPx [ 73 ]. Mechanistic studies showed that resveratrol played its therapeutic role in DKD treatment under multiple mechanisms: (1) ameliorate oxidative stress and reduce apoptosis via up-regulating AMPK expression and activity [ 74 ]; (2) regulate autophagy through overexpressing miR-18a-5p to suppress Caspase 3 [ 75 ]; (3) alleviate early-stage glomerulosclerosis via inhibiting TGF-β/Smad and ERK1/2 [ 76 ].…”
Section: Advances In Chinese Medicine In Treatment Of Dkdmentioning
confidence: 99%
“…Clinical trial revealed that the combination of resveratrol (500 mg/d) with Losartan (12.5 mg/d) reduced the urinary albumin-creatinine ratio (UACR) (–46.4 mg/g, 95% CI: −64.5 to −28.3 vs 29.9 mg/g, 95% CI: 4.9 to 54.9; p < 0.001) and increased the activity of antioxidant enzymes [ 72 ]. A meta-analysis involving 36 animal studies demon strated that resveratrol exerted its antioxidant effects by means of reducing malondialdehyde (MDA) level and restoring activities of SOD, CAT, GSH and GPx [ 73 ]. Mechanistic studies showed that resveratrol played its therapeutic role in DKD treatment under multiple mechanisms: (1) ameliorate oxidative stress and reduce apoptosis via up-regulating AMPK expression and activity [ 74 ]; (2) regulate autophagy through overexpressing miR-18a-5p to suppress Caspase 3 [ 75 ]; (3) alleviate early-stage glomerulosclerosis via inhibiting TGF-β/Smad and ERK1/2 [ 76 ].…”
Section: Advances In Chinese Medicine In Treatment Of Dkdmentioning
confidence: 99%
“…Thus, the main advantage of this molecule is highlighted, as it can target, at once, several pathophysiological mechanisms involved in the development and progression of DKD [ 137 , 139 ]. The impact on this condition is proven in vitro [ 140 ], in vivo [ 140 , 141 , 142 , 143 ] and also in small-sample clinical trials [ 144 , 145 ]. A recent systematic review and meta-analysis of animal studies [ 143 ] evaluating the effect of RES on DKD showed that several parameters are influenced by this molecule, including blood glucose levels and serum creatinine.…”
Section: Therapeutic Approaches In Diabetic Kidney Disease Via Oxidat...mentioning
confidence: 99%
“…The impact on this condition is proven in vitro [ 140 ], in vivo [ 140 , 141 , 142 , 143 ] and also in small-sample clinical trials [ 144 , 145 ]. A recent systematic review and meta-analysis of animal studies [ 143 ] evaluating the effect of RES on DKD showed that several parameters are influenced by this molecule, including blood glucose levels and serum creatinine. An interesting finding was that no side effects were reported, but this outcome should be assessed with caution, as several factors could have had an impact, including dosages and a brief administration time of the drug [ 143 ].…”
Section: Therapeutic Approaches In Diabetic Kidney Disease Via Oxidat...mentioning
confidence: 99%
See 1 more Smart Citation
“…In both animal models and DN patients, increased infiltration of circulating inflammatory mediators and immune cells into renal tissue has been observed ( 9 ). Inflammation also plays an important role in the pathogenesis of DN, such as through cell adhesion molecules, growth factors, chemokines, and proinflammatory cytokines ( 10 , 11 ). A low dose of interleukin-17A (IL-17A) can prevent DN in type 1 and type 2 diabetic models ( 12 ).…”
Section: Introductionmentioning
confidence: 99%